Evaluation of cooling effects of crushed rock under sand-filling and climate warming scenarios on the Tibet Plateau. (5th January 2016) - Yu, Wenbing; Liu, Weibo; Chen, Lin; Yi, Xin; Han, Fenglei; Hu, Da
Highlights: Field test was conducted to validate the numerical heat transfer model. Natural convection decreases with increasing of sand thickness. Thermal regime of permafrost beneath porous media is investigated. Abstract: Crushed rock has been applied to cool the permafrost foundation on the Tibet Plateau. It is facing the challenges of sand-filling and climate warming. Desertification and climate warming are a definite trend on the Tibet Plateau, which has affected the permafrost and infrastructures. This study investigated the influence of sand-filling and climate warming on the cooling effect of crushed rock on the Tibet Plateau, on the basis of a coupled finite element model of convective heat transfer and heat conduction with phase change. The model is calibrated by field measurements. The field experiment and numerical simulation reveal that natural convection in rock layer only occurs in winter season. With the increasing thickness of sand in rock layer, the critical temperature difference between the sand-free layer increases, and the Ra number decreases, and the natural convection intensity weakens gradually. At the climate warming rate of 0.052 °C a −1, the cooling effect of rock layer can counteract the negative effect of climate warming and raise the permafrost table for about the former 20 years. However, the permafrost will eventually degrade continuously, which means the crushed-rock can't be applied to maintain the permafrost foundation stability anymore under these conditions.